2017
DOI: 10.1371/journal.pone.0170858
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Quantitative Studies on the Microvasculature of the Heart of a Highly Selected Meat-Type and a Wild-Type Turkey Line

Abstract: In this study the macroscopic and microscopic structure of the heart of a fast growing, meat-type turkey line (British United turkeys BUT Big 6) and a wild-type turkey line (Canadian Wild turkey) were compared. At 8 and 16 weeks of age, 10 birds of each genotype and sex were sampled. The body mass and heart mass of the meat-type turkey both increased at a faster rate than those of the wild-type turkey. However in both turkey lines, the relative heart mass decreased slightly with age, the decrease was statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…Although the absolute heart mass of LD chickens was lower than that of Ross chickens over the entire observation period, the relative heart mass in both lines was similar and decreased continuously with age. Our results are in agreement with the findings of similar comparative studies [ 14 , 18 , 19 ] that reported that the relative heart mass of poultry diminishes with age. However, in these studies the relative heart mass of unselected chicken lines was greater than that of modern meat-type chicken lines.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Although the absolute heart mass of LD chickens was lower than that of Ross chickens over the entire observation period, the relative heart mass in both lines was similar and decreased continuously with age. Our results are in agreement with the findings of similar comparative studies [ 14 , 18 , 19 ] that reported that the relative heart mass of poultry diminishes with age. However, in these studies the relative heart mass of unselected chicken lines was greater than that of modern meat-type chicken lines.…”
Section: Discussionsupporting
confidence: 94%
“…In the present study although the LD chickens’ heart had less mass than the broilers’ heart in all age groups, more of the heart area measured was occupied by capillaries from day 28 onward, at which time the area occupied by capillaries in Ross heart decreased rapidly. Similar to our findings, wild-type turkeys had a higher capillary density compared to highly selected meat-type turkeys [14]. Our observations confirm that capillary density is negatively correlated with total heart weight, i.e.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This was not observed in Sasso birds, since this breed underwent more intensive genetic selection as compared to green-legged partridges. A significant side effect of the intensive genetic selection of high-performance meat production poultry lines has been a disruption in the balance between the relative slow growth of their organs and their extremely rapid increase in muscle mass [49,50].…”
Section: Discussionmentioning
confidence: 99%